Fragments of equality in representative politics. Issue 3 (3rd May 2016) - Saward, Michael
Abstract : Deploying a broadly interpretive approach, the article explores the extent to which, and the ways in which, equality is enacted in non-elective as well as elective representation. It argues that the fleeting and fragmentary equalities evident in non-elective representation are democratically significant, and that examining them can enhance understanding of the democratic promise and limits of different modes of representation.